Clinical profile and outcome of acute encephalitis syndrome (AES) patients treated in College of Medical Sciences-Teaching Hospital - Thapa, Lekhjung J; Twayana, RS; Shilpakar, R; Ghimire, MR; Shrestha, A; Sapkota, S; Rana, PVS (Journal of College of Medical Sciences-Nepal, 2014)
Objective: Acute encephalitis syndrome is a cause of significant morbidity and mortality in Nepal. Although Japanese encephalitis virus (JEV) was thought to be a major cause for acute encephalitis syndrome, more non-Japanese encephalitis virus cases are reported. The outcome of patients with acute encephalitis syndrome is variable. Our study was designed to study the clinical profile and outcome of patients with acute encephalitis syndrome managed in tertiary care center in central Nepal. Methods: The record of patients admitted with diagnosis of acute encephalitis syndrome,from January 2010 to December 2010 in College of Medical Sciences-Teaching Hospital (CMS-TH) was reviewed. They were classified clinically as meningitis, encephalitis and meningoencephalitis. The clinical details and reports of the patients were recorded and analyzed. Results: Total of 85 cases of meningitis and encephalitis were identified. Mean age was 19.18 years. Fifty-six (65.9%) patients were males and 29 (34.1%) were females. Sixty (70.58%) patients had meningitis, 8 (9.41%) had encephalitis, and 17 (20.0%) had meningoencephalitis. JE serology was positive in 4 patients (4.7%). Seventy-two (84.7%) patients made full recovery and were discharged from hospital. Thirteen (15.3%) patients left against medical advice (LAMA). Conclusion: Acute encephalitis syndrome is still a major public health problem in Nepal. Few of these patients have Japanese Encephalitis. There is a trend towards improved outcome because of availability of improved health services. However, financial constraint remains a challenge in management of acute encephalitis syndrome. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-2, 31-37 DOI: http://dx.doi.org/10.3126/jcmsn.v9i2.9685